2019
DOI: 10.29356/jmcs.v62i3.531
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and biological evaluation of novel fungicides for the management of Fusarium DieBack disease

Abstract: Abstract. Fusarium Dieback, a new and lethal insect-vectored disease can host over 300 tree species including the avocado trees. This problem has recently attracted the attention of synthetic chemist not only to develop new triazol antifungal agents but also due to severe drug resistance to “classic” triazol antifungal agents. Here, a series of novel antifungal triazoles with a p-trifluoromethylphenyl moiety were synthesized and characterized by spectroscopic and spectrometric methods. Most of the target compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In the phytotoxicity assay, the length of the seedling's root appeared relatively favorable when compared to previous studies involving non-encapsulated molecules, as reported by Bonilla et al (2019). The same trend was observed in the analysis of lateral roots.…”
Section: Discussionsupporting
confidence: 75%
“…In the phytotoxicity assay, the length of the seedling's root appeared relatively favorable when compared to previous studies involving non-encapsulated molecules, as reported by Bonilla et al (2019). The same trend was observed in the analysis of lateral roots.…”
Section: Discussionsupporting
confidence: 75%
“…These hosts probably do not produce allomones that deter initial attack by PSHB but can deter its colonization even after establishment of F. euwallaceae . These hosts may therefore still be vulnerable to fusarium wilt (Bonilla‐Landa et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the application of commercial chemicals for prolonged periods could result in phytotoxicity. [63][64][65] In South Africa, no insecticides or fungicides that have been evaluated with scientific rigour for efficacy in PSHB management have been registered for use.…”
Section: Mitigationmentioning
confidence: 99%